Analysis of Bank Health Level to Potential of Financial Distress Distress Using the RGEC Method (Case Study of Regional Development Banks in Indonesia for the 2019-2023 Period) - Isti Fajri Khairunnisa; Wiralestari; Friyani, Rita (Indonesian Journal of Business Analytics, 2024)
The objective of this study is to examine the financial health of Regional Development Banks in Indonesia from 2019 to 2023 using the RGEC method as proxies for the Non-Performing Loan (NPL) Ratio, Load to Deposit Ratio (LDR), Proportion of Independent Commissioners (KI), Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). Secondary data collected from all of Indonesia's regional development bank sites is utilized in this quantitative descriptive research. There were 105 pieces of company data analyzed in this study, with 21 companies making up the sample. Multiple linear regression analysis is the method used for the analysis. The SPSS software was utilized to conduct this computational analysis. Financial distress was found to be significantly affected by the following variables: Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR), but not by the Noan Performing Loan (NPL) variable, independent commissioners, Return On Assets (ROA), or Return On Equity (ROE).